PENYULUHAN PENINGKATAN KUALITAS HIDUP LANSIA MELALUI PENERAPAN POLA HIDUP SEHAT DI TANAH JAWA SIMALUNGUN - Dian Permata Nasution; Marolop Parlindungan Napitu; Yeni Trisna Purba; Isa Harpika Br. Ginting; Hendri, Hendri (Nusantara Hasana Journal, 2025)
This community service report addresses the improvement of quality of life among the elderly through a healthy lifestyle education program in Tanah Jawa Simalungun. The outreach activities encompass nutritional guidance, physical exercise, stress management, and regular health screening. The program was implemented using a participatory approach involving initial surveys, educational material development, lectures, discussions, and practical demonstrations. Evaluation results indicate significant improvement in the knowledge and awareness of the elderly regarding the importance of a healthy lifestyle, behavioral changes in daily activities, and increased participation in support groups. These findings are expected to serve as a model for other regions aiming at sustainable elderly welfare improvement.